Maximum stress and deformation of coal flow breaker plate due to continuous loading - Lubis, Asnawi; A. Hadi, Kiagus; Akmal, Jamiatul; Hasymi, Zulhendfri (BKS-TM Indonesia, 2024)
Vibrating screens are very important equipment in the coal mining and processing industry. One of the components of this vibrating screen is a flow breaker plate, which functions as a flow breaker for the coal bulk load before it falls on the vibrating screen. Due to the impact load of coal bulk, which works continuously, the plate often breaks in fatigue with a maximum stress and deformation greater than those if the load were worked statically. This paper presents the results of a finite element study on the maximum stress and deformation that occur in various materials used as coal flow impact load breaker plates at PT Bukit Asam Pelabuhan Tarahan, Bandar Lampung. The plate construction is modeled as beams with fixed ends. The length and height (as a beam) are 1500 and 200 mm, respectively, while the plate thickness (beam width) is analyzed to be 15 and 20 mm for each type of material. Four types of materials available at PT Bukit Asam, namely ST37, ST52, Hardock (HB400), and GS20 Mns, were analyzed for impact loads using ANSYS Explicit Dynamics. The results of the finite element analysis show that the ST37 material, with a thickness of 20 mm, experiences the smallest maximum stress compared to the other three types of material. Meanwhile, for deformation, the analysis results show that ST52 material with a thickness of 20 mm experiences the smallest maximum deflection compared to the three other types of material.